Evaluasi terhadap pengelolaan kelas melalui punishment dan reward pada proses pembelajaran daring di kelas II di sekolah dasar - Ichlasita, Daru Nafisyah; Marmoah, Sri; Hadiyah, Hadiyah (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
This study aims to describe the evaluation of classroom management through reward and punishment in the online learning in Class II SD Djama'atul Ichwan. The research approach used is descriptive qualitative. The data in this study are the results of interviews with grade II teacher and grade II students, observations, documentation, and teacher’s archive. Sources of data in this study were grade II teachers, grade II students, and the online learning process. Data collection techniques are carried out by observation, interviews, and documentation. The instruments used in data collection are observation tables and a list of questions. This study used interactive analysis techniques consisting of data collection, data reduction, data display, and conclusions. The validity of the data was tested by observing persistence and triangulation of data sources. The results of the study showed that, the four stages of evaluation carried out by the teacher were collecting information from various parties (teachers, students, student’s parents), self-evaluation by reflecting on the results of information collection, and periodic evaluation of methods showing good results. The level of discipline, learning motivation, learning effectiveness, student enthusiasm for learning and the conduciveness of the classroom atmosphere are optimal but no change in method was found during the study.